Implementation of a Web-Based Inventory System for Sales Efficiency in Retail Sector MSMEs in Bandung City - Makalalag, Sukiman; Soegoto, Eddy Soeryanto (International Journal of Research and Applied Technology (INJURATECH), 2025)
Indonesian Government Takes Bandung’s Retail Stores to Court The shelves should be organized. we’re looking into ways to improve stock monitoring with a web-based. We adopted a Waterfall approach for the construction of this system. When we created the stock tracking website. This study is special since we did not do that. We tried it; we actually tried it out in a shop. The system was tested by them. We wanted to see if the system would actually work well in a real situation. We tested it in. I attempted it. I witnessed what happened. This is basically the definition of black-box testing, right? I used the “Black Box” testing method to see what would happen after just kicking the tires on it. We have just seen the results. The system was working perfectly; all the businesses in Bandung that. The decision to use the web-based inventory system was 100% successful. The main thing is, once we. Our operations improved greatly when we began using it. According to our stock data, transaction timelines dropped by 83%. This new system reduced stock shortages by 90% and was 98% accurate. So, it seems like it helps. More sales and improved performance for business. It’s a fairly suitable solution for smaller and midsized.